Quo Vadis Africa? South Africa, Afrophobia and the Betrayal of Liberation Memory: CODESRIA Bulletin Online, No. 8, July 2026 - Ibrahim Abdullah, (CODESRIA Bulletin, 2026)
The latest upsurge of organised attacks against African migrants in South Africa is not merely another episode of ‘xenophobia’. That word is now too small, too polite, too analytically exhausted. What we are witnessing is something more sinister: Afrophobic vigilantism, the racialisation of immigration status and the privatisation of state power by mobs who have appointed themselves border police over Black African bodies. The so-called 30 June deadline for undocumented migrants to leave South Africa was not issued by the South African state. Yet its social force has been real. It has emptied streets, shuttered shops, split families, pushed fathers away from children, driven frightened migrants towards buses, churches, embassies and camps and placed entire communities under siege. This is precisely the scandal: a vigilante ultimatum has acquired the psychological force of law. The state may say, correctly, that it did not issue the order. But the deeper question remains: why did an unlawful ultimatum become so believable, so terrifying and so socially enforceable? Why did vulnerable Africans feel that flight was safer than waiting for constitutional protection? Here, helplessness and complicity begin to blur. A state does not need to formally endorse violence to enable it. It can enable violence through delay, ambiguity, selective enforcement, inflammatory political rhetoric and failure to protect the vulnerable before mobs become confident. When private actors can threaten removals, shut down shops, intimidate workers, inspect belonging and decide who may live in a community, the state has ceded one of its most basic obligations: the protection of persons under its jurisdiction. This is not immigration policy. It is street sovereignty. The language of ‘illegal foreigners’ pretends to be administrative but in practice it is racialised. The imagined ‘illegal’ is Black, African, poor, informal, accented, visible and vulnerable. No one can determine a person’s immigration status by looking at their face, hearing their language or seeing them trade in a township. Yet that is how this campaign works. The target is not simply the undocumented migrant. The target is African presence itself. That is why we must call this what it is: Afrophobia. It is not merely fear of the foreigner; it is hostility towards the ‘African foreigner’—a frighteningly bizarre formulation. It is the making of fellow Africans into intruders, parasites, criminals and disposable bodies. It is the return of the pass-law imagination in post-apartheid clothing: Where are your papers? Who authorised you to be here? By what right do you work, trade, rent, worship, study, love, marry, give birth, or bury your dead on this soil? This invention of an identifiable enemy has a name: Makwerekwere, also rendered as Amakwerekwere or Kwerekwere. It is derogatory, combustible and politically revealing. It names not simply the migrant but the African migrant as a figure of suspicion: the one whose language is mocked; whose accent is heard as noise; whose labour is resented; whose poverty is read as invasion; and whose body is treated as evidence of illegitimate presence. The slur performs the violence before the violence becomes physical. To call someone Makwerekwere is to reduce a person to a category that can be collectively identified, policed, expelled or attacked. It creates the fantasy that the ‘problem’ has a face, a sound, a gait, a shopfront, a nationality, a street corner. This is why the language matters. Naming is not innocent. In moments of mass fear, a derogatory name becomes a weapon; it compresses history, rumour, resentment and state failure into a single disposable body. This grammar is unmistakeably familiar: it references Frantz Fanon in his 1961 classic, The Wretched of the Earth. Scholars have long warned of this. David Mario Matsinhe’s influential article, ‘Africa’s Fear of Itself: The Ideology of Makwerekwere in South Africa’ (2011),1 argues that the usual language of xenophobia misses the deeper colonial and racial history that shapes hostility towards African foreign nationals. Recent scholarship on xenophobia as structural violence similarly notes that the pejorative terminology of Makwerekwere or Kwerekwere encapsulates the construction of the ‘Black foreigner’ as the undesirable Other. The term therefore is at the centre of any serious account of South African Afrophobia. The tragedy is that this Afrophobia is currently unfolding in Africa’s quintessential settler state! South Africa’s liberation was not produced by South Africans alone. The freedom of South Africa was carried by exiles, workers, students, churches, diplomats, soldiers, journalists, trade unionists, artists and ordinary Africans across the continent. It was sustained by Nigeria’s enormous diplomatic, financial and moral weight. It was supported by the steadfastness of the Frontline States: Mozambique, Angola, Zambia, Zimbabwe, Tanzania, Botswana, Lesotho, Malawi and others which shouldered the burdens of proximity, retaliation, destabilisation, refugees, raids and economic sabotage. These countries did not pay those costs so that a liberated South Africa could one day become a theatre of African humiliation. Nigeria did not carry the anti-apartheid burden so that Nigerians, Zimbabweans, Malawians, Mozambicans, Congolese, Basotho, Zambians, Ghanaians, Tanzanians and other Africans could later be hunted under the banner of immigration control. Mozambique and Angola did not endure destabilisation so that post-apartheid South Africa could normalise the persecution of African migrants. Zambia did not host political exiles so that African refuge could later be treated as contamination. Zimbabwe did not stand in the liberation line so that its citizens could become convenient scapegoats for South Africa’s unresolved crises. This is why the speech on 22 May 2026 by former President Thabo Mbeki matters.2 Mbeki was not speaking merely as a retired statesman. He was speaking from the memory of exile, struggle and continental solidarity. His warning must be taken seriously. Anti-migrant violence is not only a human rights crisis; it is a crisis of memory. It erases the sacrifices that made South African freedom possible. It mocks the language of Pan-Africanism. It converts the former beneficiaries of African solidarity into agents, spectators or apologists of African dispossession. Of course, South Africa faces real crises: unemployment, inequality, crime, corruption, housing shortages, weak border management, overwhelmed public services and deep post-apartheid frustration. These crises are not imaginary. But the African migrant did not create the structural failures of the post-apartheid state. The migrant did not design corruption. The migrant did not engineer unemployment. The migrant did not loot municipalities. The migrant did not collapse hospitals. The migrant did not betray land reform, industrial policy, public safety or service delivery. The migrant is being made into a portable explanation for governance failure. This is the oldest trick of distressed politics: when the powerful cannot answer for suffering, they redirect anger towards those with even less protection. The poor are encouraged to fight the poor. Workers are told that other workers are the enemy. Citizens are taught to see migrants as thieves of jobs, rather than to ask who controls capital, who exploits undocumented labour, who benefits from informality, who profits from broken systems and who uses nationalist rage to escape accountability. A scapegoat is not a diagnosis. It is a political narcotic. If South Africa is serious about immigration governance, then it must govern through law, not mob ultimatum. Immigration enforcement belongs to lawful institutions, not vigilante formations. Documentation status must be determined by competent authorities, not by accent, skin, surname, language, neighbourhood or rumour. Deportation, where lawful, must follow due process. Asylum seekers must be protected. Children must not be punished for the status of parents. Shops must not be destroyed. Clinics must not become checkpoints. Schools must not become border posts. Landlords must not become deportation officers. Citizens must not be recruited into the moral laziness of hunting the vulnerable. Pan Africanism now faces a test more serious than conference speeches and commemorative slogans. It must decide whether it is a living ethic or a museum language. If Pan Africanism means anything, it must mean that Africans are not disposable in Africa. It must mean that colonial borders, however legally real, cannot become instruments for stripping Africans of humanity. It must mean that the memory of anti-apartheid solidarity imposes obligations on the present. It must mean that South Africa’s freedom carries a debt, not of subordination but of moral reciprocity. To say this is not to deny South Africa’s sovereignty. It is to insist that sovereignty cannot be a licence for Afrophobic abandonment. Citizenship matters. Borders matter. Law matters. But none of them matters more than the human being. A person who lives, works, rents, worships, studies, trades, loves, raises children and contributes to the social life of a place has entered the moral community of that place. Their paperwork may need regularisation. Their status may require legal determination. But their humanity is not pending. Africa must now ask itself: Quo vadis? Where are we going? Are we becoming a continent where liberation histories are remembered only when convenient? Are we going towards a politics where African governments celebrate continental unity at summits while abandoning their citizens to mob violence abroad? Are we moving towards a future where the African poor are divided by colonial borders while elites move freely with diplomatic passports, offshore accounts and private security? Are we becoming a continent where apartheid is condemned as history, but its pass-law imagination is reproduced against migrants? Or are we prepared to build a serious continental ethic of protection? A serious response must be immediate and structural. African governments whose citizens are threatened must do more than evacuate. They must demand protection, investigation, compensation and prosecution. The African Union and SADC must treat Afrophobic violence as a continental governance issue, not a domestic embarrassment to be managed quietly. South African civil society, churches, unions, universities, lawyers, journalists and community leaders must refuse the criminalisation of African presence. Labour movements must organise citizens and migrants together, because undocumented vulnerability is also a weapon against all workers. Employers who exploit migrants must be punished. Politicians who incite hatred must be named. Vigilante groups must be dismantled through law. Above all, South Africa must be reminded that its liberation memory is not ornamental. It is binding. Apartheid once made Black South Africans foreigners in their own land. It demanded passes, permissions, removals, segregated space and controlled movement. Post-apartheid South Africa must not repeat that wrong by making other Africans foreigners to humanity. The deepest betrayal would be to inherit the border logic of apartheid and turn it against those whose countries helped to defeat apartheid. As the Preamble to the Constitution of the Republic of South Africa states: ‘South Africa belongs to all those who live in it’.3 The question is no longer whether South Africa remembers Africa. The question is whether South Africa’s memory can still produce justice. Notes 1 Matsinhe, D.M., 2011, ‘Africa’s Fear of Itself: The Ideology of Makwerekwere in South Africa’, Third World Quarterly, Vol. 32, No. 2, pp. 295–313. See also Nyamnjoh, F., 2006, Insiders and Outsiders: Citizenship and Xenophobia in Contemporary Southern Africa, Dakar, London and Pretoria: CODESRIA / Zed Books / UNISA. 2 Africa Web TV, 2026, ‘Xenophobia – Africans are chasing ghosts’, YouTube. https://www.youtube.com/watch?v=KXa_ZZtWj9I 3 https://www.gov.za/documents/constitution/constitution-republic-south-africa-1996-preamble-07-feb-1997